Association of Some High-Risk Mucosal Types of Human Papillomavirus with Cutaneous Squamous Cell Carcinoma in an Iranian Population - Hassan Ehteram; Mohaddeseh Sadat Mousavian; Tahereh Mazoochi; Tahereh Khamehchian; Mohammad Karimian (Iranian Society of Pathology, 2019)
Background & Objective: Squamous cell carcinoma (SCC) is the second most common non-melanoma skin cancer that may be caused by Human papillomavirus (HPV), especially in immunosuppressed patients. However, the role of the mucosal types of HPV in SCC patients with normal immunity has not been extensively confirmed. The aim of this study was to investigate the association of some high-risk mucosal types of HPV with cutaneous SCC in an Iranian population. Methods: Sixty-five formalin-fixed, paraffin-embedded tissue specimens with a diagnosis of cutaneous SCC as the case group and sixty-five healthy skin specimens as the control group were included in our case-control study. Genomic DNA was extracted from tissue samples and then PCR was used for the detection of HPV genotypes by a commercial kit. Result: Our data revealed that 6 out of 65 SCC samples (9.2%) were infected by high-risk mucosal types of HPV whereas none of the 65 control samples were infected by the mentioned HPVs. Statistical analysis showed a significant association between these types of HPV infection and SCC risk in our studied population (P=0.028). Conclusion: These findings suggested that some high-risk mucosal types of HPV are significant risk factors for cutaneous SCC.